2002
DOI: 10.1079/bjn2001512
|View full text |Cite
|
Sign up to set email alerts
|

n-3 Fatty acids and lipid peroxidation in breast cancer inhibition

Abstract: Long-chain n-3 fatty acids (FA) consistently inhibit the growth of human breast cancer (BC) cells both in culture and in grafts in immunosuppressed mice. Large cohort studies have, however, failed to confirm a protective effect for fish oils rich in n-3 FA against BC risk. The present review examines new evidence on biological mechanisms which may be involved in the inhibition of mammary carcinogenesis by long-chain n-3 FA, focusing on an apoptotic effect by its lipid peroxidation products. Dietary intake of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 61 publications
1
54
0
3
Order By: Relevance
“…Biochemical mechanisms for the antitumor properties of n-3 PUFA are still unclear but may include changes in eicosanoid metabolism, reduction in oncogene expression, and modulation of lipid peroxidation (reviewed in refs. 12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical mechanisms for the antitumor properties of n-3 PUFA are still unclear but may include changes in eicosanoid metabolism, reduction in oncogene expression, and modulation of lipid peroxidation (reviewed in refs. 12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, ecological studies have suggested that higher intake of fish rich in n-3 HUFAs is correlated with a lower cancer incidence in several sites. 4,5 Regarding suppression of carcinogenesis, n-3 HUFAs have been proposed to play critical roles in: (i) inhibition for biosynthesis of eicosanoids (e.g., prostaglandin E 2 ) via the arachidonic acid (AA, 20:4n-6) cascade 1,6 ; (ii) modulation of gene expression or the activities of signal transduction molecules involved in the control of cell growth, differentiation, apoptosis, angiogenesis and metastasis [7][8][9] ; (iii) estrogen metabolism 1 ; (iv) production of free radicals and reactive oxygen species; 7,8,10,11 (v) modulation of insulin sensitivity 1,12 and (vi) membrane fluidity. 1 For the AA cascade, such potential activities of EPA and DHA are estimated to be approximately 5 times higher than that of 18:3n-3.…”
mentioning
confidence: 99%
“…Furthermore, there is evidence that mouse mammary tumors are more sensitive than normal tissues to the induction of reactive oxygen species-mediated apoptosis (33) and that developing tumors in vivo are inherently susceptible to dietinduced increased oxidative stress resulting in decreased tumor growth and progression (33,34). It has been proposed that the protective effect of dietary ˆ-3 fatty acids against mammary tumor development may be due to the presence of lipid peroxidation products arising from the peroxidation of -3 fatty acids (35). Therefore, reactive oxygen species may have dual roles whereby low levels result in normal protective signaling, intermediate levels lead to a variety of cellular damage promoting tumorigenesis and high levels could promote oxidative burst and cell death (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%